2011
DOI: 10.1063/1.3670053
|View full text |Cite
|
Sign up to set email alerts
|

Germanium fin light-emitting diode

Abstract: We propose a germanium fin light-emitting diode for a monolithic light source on a Si photonics chip. The germanium fins were fabricated by the oxidation condensation of silicon-germanium sidewalls epitaxially grown on silicon fins. We found that a tensile stress is applied to the pure germanium fins by the difference of the thermal expansion coefficient with that of the surrounding oxide. The electroluminescence spectra were consistent with those expected from direct recombination in germanium with a tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 20 publications
(32 reference statements)
1
35
0
Order By: Relevance
“…11(a), photoluminescence (PL) measurements under a high excitation (4 mW of 457-nm laser light with ∼2 µm in diameter) showed a light emission around 1.55 µm from Ge layers on Si as well as from bulk Ge. Electroluminescence (EL) can be also obtained for vertical Ge pn diodes on Si under forward biases [40,41,42] and for lateral pn diodes of Ge fabricated with standard CMOS processes [43,44]. Fig.…”
Section: Prospects For On-chip Light Sourcesmentioning
confidence: 99%
“…11(a), photoluminescence (PL) measurements under a high excitation (4 mW of 457-nm laser light with ∼2 µm in diameter) showed a light emission around 1.55 µm from Ge layers on Si as well as from bulk Ge. Electroluminescence (EL) can be also obtained for vertical Ge pn diodes on Si under forward biases [40,41,42] and for lateral pn diodes of Ge fabricated with standard CMOS processes [43,44]. Fig.…”
Section: Prospects For On-chip Light Sourcesmentioning
confidence: 99%
“…Direct-gap emission efficiency is sensitive to the crystalline quality, and it was found that the carrier lifetime seems to be limited by non-radiative recombinations [1], [7]. Consequently, ion-implantation may not be suitable for Ge light emission applications.…”
Section: Spin-on Dopingmentioning
confidence: 99%
“…[9][10][11][12] Ge is an indirect band gap semiconductor, but by filling the indirect L valleys in the conduction band, we can observe direct recombination at the  point. 10) A practical Ge LD is considered as the only missing component to realize a fully monolithically integrated Si photonics link, 13) as the other necessary photonic components, like high efficiency near-IR photo-detectors, 14) modulators, 15) and waveguides, 16) have been demonstrated and are well established.…”
Section: Introductionmentioning
confidence: 99%
“…17,18) These crystalline defects will work as non-radiative recombination centers and reduce the lightemission efficiency. 13) Therefore, it is necessary to develop a process for high donor doping in Ge while minimizing the damage in the crystal lattice, 10) and enable the fabrication of a high efficiency Ge LD. 19) In fact, lasing from Ge by optical pumping, 20) and electrical pumping, 21) were reported.…”
Section: Introductionmentioning
confidence: 99%